2011
DOI: 10.5230/jgc.2011.11.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 7th UICC TNM Staging System of Gastric Cancer

Abstract: Since January of 2010, the seventh edition of UICC tumor node metastasis (TNM) Classification, which has recently been revised, has been applied to almost all cases of malignant tumors. Compared to previous editions, the merits and demerits of the current revisions were analyzed. Many revisions have been made for criteria for the classification of lymph nodes. In particular, all the cases in whom the number of lymph nodes is more than 7 were classified as N3 without being differentiated. Therefore, the coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Clinically, gastric cancer can be divided into four stages [13], which are closely associated with patient outcomes and widely used for patient treatment options. Stage I disease has tumors mostly within the stomach mucosa (IA has no lymph node spread whereas IB has one to two lymph node spread in stomach).…”
Section: Molecular Classification Of Gastric Cancermentioning
confidence: 99%
“…Clinically, gastric cancer can be divided into four stages [13], which are closely associated with patient outcomes and widely used for patient treatment options. Stage I disease has tumors mostly within the stomach mucosa (IA has no lymph node spread whereas IB has one to two lymph node spread in stomach).…”
Section: Molecular Classification Of Gastric Cancermentioning
confidence: 99%
“…Some revisions have been made for the classification of lymph nodes (12). Our study is based on data between 2007 and 2011, so TNM revision may influence results of our study by modification in N category.…”
Section: Discussionmentioning
confidence: 99%
“…After using LRS, the number of 16 LNs was achieved in one case, and 19 LNs in the other, enabling a more secure staging, despite the fact that the (15) 31.6 pN classification did not change. Several studies described in the literature concluded that there must be 16 or more LNs analyzed for pN0 staging to be achieved (1,16,21,27,31) . Son et al (31) analyzed the survival rate of 10,010 patients and concluded that when 15 or less LNs are examined and findings show no metastases (classified pN0 by TNM system), it is not possible to appropriately predict the survival of patients undergoing curative gastrectomy.…”
Section: Discussionmentioning
confidence: 99%